WATERFALL METHOD OF WEB-BASED SYSTEM TO DEVELOP WAREHOUSE PACKING EFFECTIVELY - Saopan, Muhamad Addrian (Asia Information System Journal, 2023)
This study aims to develop an efficient Warehouse Packing System for PT Luna Technology Group in order to improve operational efficiency and minimize packing errors in logistics processes. The research adopts the Waterfall Method, employing a systematic approach that encompasses requirements analysis, system design, implementation, and testing. Data was collected through qualitative observational methods, including interviews and direct observations of the existing packing processes. The findings demonstrate that the implementation of a web-based packing system significantly reduces packing times, mitigates errors in item selection, and lowers operational costs compared to the previous manual methods. The research concludes that embracing a structured software development methodology not only enhances the packing process, but also positions PT Luna Technology Group as a competitive player in the logistics industry, underscoring the need for continuous technological advancements in warehouse management.